How conflict shapes women's roles and aspirations: Insights from Nigeria - Carrillo, Lucia; Amare, Mulubrhan; Kosec, Katrina; Kyle, Jordan (CGIAR System Organization, 2024)
Conflicts affect everyone, yet the ways they affect men and women often vary significantly. In rural communities of Southwest Nigeria, where recent farmer-herder clashes have grown increasingly violent, fueled by dwindling resources and climate shocks, women have been taking on new responsibilities within their households and communities. With more men actively involved in armed groups, women often must step into roles traditionally held by men, such as running businesses or advocating for their communities. While these shifts offer opportunities for empowerment and independence, they also place considerable extra pressure on women. How do women themselves feel about this?